2009
DOI: 10.1002/hep.23410
|View full text |Cite
|
Sign up to set email alerts
|

Huh-7: A human “hemochromatotic” cell line

Abstract: Hereditary hemochromatosis (HC) is commonly associated with homozygosity for the cysteineto-tyrosine substitution at position 282 (C282Y) of the HFE protein. This mutation prevents HFE from binding beta 2 -microglobulin (beta 2 M) and reaching the cell surface. We have discovered that a widely used hepatoma cell line, Huh-7, carries a HFE mutation similar to that associated with human HC. By HFE gene sequencing of Huh-7 genomic DNA, we found a TAC nucleotide deletion (c. 691_693del) responsible for loss of a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 22 publications
5
29
0
Order By: Relevance
“…All of the above observations were found to occur independent of p53 status of the cells. We also observed potent cytotoxicity of TSC24 in Huh7 cells (data not shown), another HCC cell line carrying a HFE mutation similar to that associated with human HH (43). Our findings suggest that TSC24 exerts its anticancer effects in a HFE-independent manner.…”
Section: Discussionsupporting
confidence: 59%
“…All of the above observations were found to occur independent of p53 status of the cells. We also observed potent cytotoxicity of TSC24 in Huh7 cells (data not shown), another HCC cell line carrying a HFE mutation similar to that associated with human HH (43). Our findings suggest that TSC24 exerts its anticancer effects in a HFE-independent manner.…”
Section: Discussionsupporting
confidence: 59%
“…Huh-7 cells are hepatic carcinoma cells which are very useful for primary drug screening in vitro. 15 We observed that both the EA and ME extracts of MP seed possessed antiproliferative action at lower concentration (1 mg/ml) whereas the PE extract had no such effect. The PE extract was not examined in the other assays due to its poor antiproliferative activity.…”
Section: Discussionmentioning
confidence: 70%
“…These replicon cells were derived from the Huh7 cell line. Huh7 cells carry an HFE mutation (Y231 del), which is associated with human hemochromatosis [33]. As a conesquence of the significant problems associated with using HCV replicon to investigate iron-mediated processes, HepG2 cells treated with DEM were used as the model system in our study.…”
Section: Discussionmentioning
confidence: 99%